Optimization of glucose production from enzymatic hydrolysis of rice straw using response surface methodology - Aznizan, Shaari (2010)
Production cost of cellulase enzyme is very expensive.A research to reduce the cost by optimization of pH, temperature and agitation rate on production of glucose from enzymatic hydrolysis of rice straw by cellulose from Aspergillus niger using Response Surface Methodology(RSM) was successfully done.At the first stage of experiment, one factor at a time was employed to screen the best range for pH,temperature and agitation rate.All of the parameters ranges obtained were used in RSM.Response Surface Methodology in Design Expert version 6.0.8 software was used with Central Composite Design(CCD)mode.Seventeen sets of experiments with different parameters values were suggested by the software. The predicted optimum values for pH, temperature, agitation rate and concentration of glucose were 4.23,43oC, 177 rpm and 10.146 g/L respectively.One set of experiment was run using the optimized parameter and as a result,9.9835 g/L concentration of glucose was recorded. Before optimization,concentration of glucose was only 5.5622 g/L and the concentration of glucose was increased by 44% after optimization.The optimization also reduces the energy consumption as the temperature was reduced from 45oC to 43oC and agitation rate reduced from 180 to 177 rpm.As conclusion,this research is successful to increase the concentration of glucose production,reduce the energy consumption and also be able to reduce the cost of production